Subsídios para a resolução de conflito pelo uso dos recursos hídricos: o caso da bacia hidrográfica do Ribeiro Bonito, em Caeté - MG - Costa, Patrícia Gaspar (2019)
Conflicts over the of use water have worsened in recent years, due either to more intensive uses of water resources or changes in local or regional hydrological cycle. Brazilian federal law warrants the granting of water use rights as an instrument for the management of water resources. The granting act assures its beneficiary a right to use a specific water discharge, calculated in consideration of water availability and demand, while delegating to a specific governmental agency the enforcement of that use. In Minas Gerais, the State Water Management Institute (IGAM) is charged with implementing water resource policies, and also acts as mediator of conflicts involving water use actors such as city suppliers, irrigated farms, industrial users and others. The Ribeiro Bonito watershed, a creek tributary to the Velhas River, inserted in the Water Resources Planning and Management Unit SF5, was declared by IGAM in 2007 as in a state of conflict for water use, requiring thus regulation by means of a collective granting act. In this context, the present work was carried out with the objective of analyzing the water conflict situation and the effectiveness of the Collective Granting Act nº 3.268/2017, as well as providing a watershed environmental diagnosis with soil studies and a poll with water users. The results led to the conclusion that the collective granting act of water use rights did not settle the conflict in the basin. It is suggested to: strengthen the representativeness of water users and the collective interest; to estimulate soil and water conservation practices in the rural properties; to start measuring water discharges; and to seek new alternatives for water supply to meet the demand in the city of Caeté. Thus, several coordinated actions can reduce conflicts, increase soil and water conservation, and prioritize the local management of water resources.